Self-sufficiency of personality: the nature of psychological phenomenon - Bugaitsova, A. S. (ҚазҰУ Хабаршысы. Психология және әлеуметтану сериясы, 2015)
Given article describes the main results of the theoretical and methodological research of the nature of selfsufficiency. The author reveals the basic problems of understanding of selfsufficiency, the complexity of its categorical apparatus, and especially the definition of the phenomenon. As indicated the main nuances in the study of the given phenomenon, among which the ambiguity of the interpretations of the concept, the un certainty of the criteria of selfsufficiency, its structural characteristics and aspectual classification. The historical inquiry of the investigation of the phenomenon from the standpoint of the representatives of the schools of philosophy and different approaches of scientific psychological areas is presented as well.On the basis of the etymological approach the variations of definitions of selfsufficiency were analyzed. Also found identical with selfsufficiency psychological phenomena that are directly or indirectly indicate the term.